2006
DOI: 10.1002/pd.1415
|View full text |Cite
|
Sign up to set email alerts
|

Fetal enterolithiasis: prenatal sonographic and MRI diagnosis in two cases of urorectal septum malformation (URSM) sequence

Abstract: The prenatal detection of enterolithiasis carries a poor prognosis. Most of the previously reported cases were invariably associated with major fetal malformations of the urinary and gastrointestinal tract. It is a warning sign for large bowel obstruction with or without enterourinary fistula. Therefore, adequate gastrointestinal and urologic studies must be undertaken after birth for the final diagnosis. There is a high mortality rate in the reported cases, mostly attributed to associated anomalies, and all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 26 publications
1
27
0
2
Order By: Relevance
“…It has been suggested that the intraluminal meconium calcifications results from the mixing of meconium and fetal urine in a low pH condition [9]. Interestingly, most patients with imperforate anus and rectourinary fistula have no enterolithiasis on preoperative radiologic evaluations [1]. Most likely this is because no significant mixing of stool and urine occurs when urinary outflow through the urethra is unobstructed.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been suggested that the intraluminal meconium calcifications results from the mixing of meconium and fetal urine in a low pH condition [9]. Interestingly, most patients with imperforate anus and rectourinary fistula have no enterolithiasis on preoperative radiologic evaluations [1]. Most likely this is because no significant mixing of stool and urine occurs when urinary outflow through the urethra is unobstructed.…”
Section: Discussionmentioning
confidence: 97%
“…Intraluminal calcification of meconium usually results from the mixing of urine and meconium in utero. The association of intraluminal meconium calcifications and distended bowel loops should raise the suspicion of a combined malformation of urological and gastrointestinal tract [1].…”
mentioning
confidence: 99%
“…It was suggested that the presence of fetal urine was associated with a change in the calcium phosphate product in the meconium that results in enterolithiasis. Some authors state that mixing of urine and meconium is essential for the precipitation of those stones because most cases of enterolithiasis were reported in anal atresia with rectourinary fistula [2]. In contrast, some have argued that although in normal fetuses the mixture of meconium and urine in the fetal bowel is a physiologic phenomenon, enterolithiasis does not occur [3,4].…”
Section: Literature Reviewmentioning
confidence: 97%
“…URSMS has characteristic features that can be detected by fetal ultrasonography or magnetic resonance imaging [6,7] , such as a prominently dilated cloaca and oligohydramnios, which is so similar to urethral obstruction or stenosis. Sometimes, intestinal calcification formed by urinary reflux into the intestinal lumen is detected [6] .…”
Section: Discussionmentioning
confidence: 99%